Myxomycetes (Physarum) Physarum bogoriense - Kryvomaz, Т. І.; Minter, D. W.; Michaud, A. (СABI, 2017)
Diagnostic features. Often associated with Physarum bivalve Pers., but distinguishable by the yellow or brown colour, the rounded plasmodiocarps on narrow bases, and dehiscence by triangular lobes instead of valves; spores are usually paler and smaller than those of P. bivalve; sporocarps of P. bivalve are strongly compressed laterally, and even when nearly terete are always much taller than wide. Differs from P. bitectum G. Lister which has white plasmodiocarps and clearly spinose spores 10–13 µm diam. Differs from P. aeneum (Lister) R.E. Fr. which has yellow or brown lime in the capillitium. In some collections, sporocarp shape and colour call to mind P. retisporum G.W. Martin, but that species can be distinguished by its reticulate spores.
Keywords: myxomycetes; міксоміцети; Physarum bogoriense